Tax Avoidance Behavior And Tax Aggressiveness Of Energy Sector Companies Before And After Implementation Of The Voluntary Disclosure Program - Ramadhan, Muhammad Agra; Maheksa , Tita Melan; Firmansyah, Amrie (Politeknik Keuangan Negara STAN, 2023)
This study examines differences between tax avoidance and tax aggressiveness in energy sector companies before and after the Voluntary Disclosure Program (PPS implementation). The method in this study is quantitative, using secondary data derived from financial statements listed on the Indonesia Stock Exchange (IDX) via the website www.idx.co.id. The data employed in this study are the financial statements of energy sector companies in 2020 and 2021. Hypothesis testing was carried out using the Wilcoxon difference test with a purposive sampling method of 44 observations. The result of this research is the existence of a voluntary disclosure program which is one of the programs in the Tax Regulation Harmonization Act which indirectly has an impact on tax avoidance and tax aggressiveness by publicly listed companies in Indonesia in the energy sector. The Wilcoxon test that has been carried out shows that 13 of the 22 samples experienced an increase in the value of ETR in 2021, which indicates an increase in the tax expenses incurred by the company due to the implementation of the Voluntary Disclosure Program (PPS). The PERMDIFF test results conclude that 20 of the 22 samples suggest a decrease in PERMDIFF in 2021, indicating that the company reduced the tax aggressiveness due to the Voluntary Disclosure Program (PPS).